Proposal Sustainability Assessment of Resource Sharing in Intermodal Freight Transport with Agent-based Simulation. Issue 3 (2015) - Furtado, Pedro; Frayret, Jean-Marc
Abstract: Despite of the importance of the freight transportation at the world economy, this industry is not economic, social and environmental friendly. Based on the collaborative methodology, this article only introduces some aspects of the resource sharing intermodal transportation model. This model was created and its next step is to assessment the impact of resource sharing of intermodal freight transportation. We present the general resource sharing intermodal transportation model and simulation model, as well, the performance indicators to evaluate the freight network performance.